Discriminating between Interstitial and Circulating Leukocytes in Tissues of the Murine Oral Mucosa Avoiding Nasal-Associated Lymphoid Tissue Contamination - Bittner-Eddy, Peter D.; Fischer, Lori A.; Tu, Andy A.; Allman, Daniel A.; Costalonga, Massimo (Frontiers in Immunology, 2017)
Periodontitis is a chronic inflammatory response to a microbial biofilm that destroys bone and soft tissues supporting the teeth. Murine models of periodontitis based on Porphyromonas gingivalis colonization have shown that extravasation of leukocytes into oral tissue is critical to driving alveolar bone destruction. Identifying interstitial leukocytes is key to understanding the immunopathogenesis of periodontitis. Here we describe a robust flow cytometry assay based on intravenous FITC-conjugated anti-mouse CD45 mAb that distinguishes interstitial leukocytes in the oral mucosa of mice from those circulating within the vasculature or in post-dissection contaminating blood. Unaccounted circulating leukocytes skewed the relative frequency of B cells and granulocytes and inflated the numbers of all leukocyte cell types. We also describe a dissection technique that avoids contamination of oral mucosal tissues with nasal-associated lymphoid tissues (NALT), a B cell rich organ that can inflate leukocyte numbers at least 10-fold and skew the assessment of interstitial CD4 T cell phenotypes. Unlike circulating CD4 T cells, interstitial CD4 T cells were almost exclusively antigen experienced cells (CD44hi). We report for the first time the presence of antigen experienced Pg-specific CD4 T cells in NALT following oral feeding of mice with Pg. This new combined flow cytometry and dissection approach allows identification of leukocytes infiltrating the connective tissues of the murine oral mucosa and avoids confounding analyses of leukocytes not recruited to inflamed oral mucosal tissues in disease conditions like periodontitis, candidiasis or sialadenitis.